Exposure to hardly soluble indium compounds in ITO production and recycling plants is a new risk for interstitial lung damage. Issue 1 (11th July 2007) - Hamaguchi, T; Omae, K; Takebayashi, T; Kikuchi, Y; Yoshioka, N; Nishiwaki, Y; Tanaka, A; Hirata, M; Taguchi, O; Chonan, T
Abstract : Objectives: To identify the effects of indium on the lung and to assess exposure-effect and exposure-response relations between indium exposure and effects on the lungs. Methods: Ninety three male indium exposed and 93 male non-exposed workers from four ITO manufacturing or ITO recycling plants were analysed in a cross-sectional study. Indium in serum (In-S) was determined as a biological exposure index. Geometric means (GSD) of In-S were 8.25 ng/ml (4.55) in the exposed workers and 0.25 (2.64) in the non-exposed workers. The maximum concentration of In-S was 116.9 ng/ml. A questionnaire for respiratory symptoms and job histories, spirometry, high-resolution computerised tomography (HRCT) of the chest, serum KL-6, serum SP-A, serum SP-D and serum CRP were measured as the effect indices. Results: Spirometry, subjective symptoms and the prevalence of interstitial or emphysematous changes on lung HRCT showed no differences between exposed and non-exposed workers. Geometric means (GSD) of KL-6, SP-D and SP-A in the exposed workers were 495.4 U/ml (2.26), 85.2 ng/ml (2.02) and 39.6 ng/ml (1.57), and were significantly higher than those in the non-exposed workers. The prevalence (%) of the exposed and non-exposed workers exceeding the reference values were also significantly higher in KL-6 (41.9 vs 2.2), SP-D (39.8 vs 7.5), and SP-A (43.0 vs 24.7). Very sharp exposure-effect and exposure-response relations were discovered between In-S and KL-6 and between In-S and SP-D when the exposed workers were classified into seven groups by In-S. Conclusions: The study outcomes with regard to the basis of serum immunochemistry biomarkers and HRCT indicate that exposure to hardly soluble indium compound dust may represent a risk for interstitial lung damage.